A study on factors that influence employees’ performance in marketing department at Telekom Malaysia Berhad Seremban Negeri Sembilan / Faeza Zainal Abidin - Abidin, Faeza Zainal (Faculty of Business and Management, 2009)
This project paper is about a study on THE FACTORS THAT INFLUENCE EMPLOYEES’ PERFORMANCE IN MARKETING DEPARTMENT AT TELEKOM MALAYSIA BERHAD, SEREMBAN NEGERI SEMBILAN. The important of this research is to identify the potential factors that will contribute to the performance of employees in Marketing Department at Telekom Malaysia Berhad, Negeri Sembilan and to measure how the employees satisfied with the reward systems, training, leadership and workload at the company. Since the employees’ performance is one of the major problem that usually facing by the company, performance improvement should be given priority.